2022
DOI: 10.3389/fbioe.2022.994134
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a suitable photosynthetically active microalgae strain for the co-cultivation with mammalian cells

Abstract: Preventing hypoxic zones in 3D bioprinted mammalian cell-laden constructs using an internal oxygen supply could enable a more successful cultivation both in vitro and in vivo. In this study, the suitability of green microalgae as photosynthetic oxygen generators within bioprinted constructs was evaluated by defining and investigating important parameters for a successful co-culture. First, we assessed the impact of light–necessary for photosynthesis–on two non-light adapted mammalian cell types and defined red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…3D bioprinting was investigated as a manufacturing method to produce LBM, since recent studies analyzing 3D bioprinting of bacteria, such as Escherichia coli (Lehner et al, 2017), Bacillus subtilis (Huang et al, 2019), or Acetobacter xylinum (Schaffner et al, 2017), demonstrated good cell viability and functionality over days up to several weeks. A blend of alginate and methylcellulose (algMC) was chosen as the hydrogel matrix of the LBM because it is a well-established bioink for extrusionbased bioprinting that exhibits high biocompatibility with various mammalian and non-mammalian cell types (Lode et al, 2015;Ahlfeld et al, 2017;Schütz et al, 2017;Dani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D bioprinting was investigated as a manufacturing method to produce LBM, since recent studies analyzing 3D bioprinting of bacteria, such as Escherichia coli (Lehner et al, 2017), Bacillus subtilis (Huang et al, 2019), or Acetobacter xylinum (Schaffner et al, 2017), demonstrated good cell viability and functionality over days up to several weeks. A blend of alginate and methylcellulose (algMC) was chosen as the hydrogel matrix of the LBM because it is a well-established bioink for extrusionbased bioprinting that exhibits high biocompatibility with various mammalian and non-mammalian cell types (Lode et al, 2015;Ahlfeld et al, 2017;Schütz et al, 2017;Dani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…3D bioprinting was investigated as a manufacturing method to produce LBM, since recent studies analyzing 3D bioprinting of bacteria, such as Escherichia coli ( Lehner et al, 2017 ), Bacillus subtilis ( Huang et al, 2019 ), or Acetobacter xylinum ( Schaffner et al, 2017 ) , demonstrated good cell viability and functionality over days up to several weeks. A blend of alginate and methylcellulose (algMC) was chosen as the hydrogel matrix of the LBM because it is a well-established bioink for extrusion-based bioprinting that exhibits high biocompatibility with various mammalian and non-mammalian cell types ( Lode et al, 2015 ; Ahlfeld et al, 2017 ; Schütz et al, 2017 ; Dani et al, 2022 ). Alignate as a natural polymer has been used as an additive to mortar in several studies, which resulted in an increased compressive and tensile strength ( Susilorini et al, 2014 ; Mohesson and Abbas, 2020 ) and enhances the building materials flame-, fire-, and heat-resistance significantly ( DeBrouse, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The blends consisting of 3 wt% alginate and 9 wt% methylcellulose (Alg-MC) were prepared and laden with the different cell types at room temperature; cell densities were chosen based on our previous studies. [11,12,15,18,20,22,26] One aliquot of each bioink was filled into a cartridge for immediate use for extrusionbased bioprinting without storage (W0), four aliquots were filled into separate cartridges and the four cartridges were transferred to 4°C for storage. After 1-4 weeks of storage (W1-W4), the cartridges were brought to room temperature and used for bioprinting.…”
Section: Resultsmentioning
confidence: 99%
“…The high viability (≈ 90% observed for W0) and the growth of embedded C. vulgaris after bioprinting in Alg-MC is consistent with the findings for other bioprinted microalgae such as C. reinhardtii, Chlorella sorokiniana and Scenedesmus sp. [17,18,40] The storage at 4°C can be expected to have a stronger impact on the living part of bioinks, the cells. For the microalgae, only a marginal decrease of viability throughout the 7 days of cultivation, due to cold storage of the bioink was detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation